Perceptions of Local Environmental Issues and the Relevance of Climate Change in Nepal's Terai: Perspectives From Two Communities - Nash, Nick; Capstick, Stuart; Whitmarsh, Lorraine; Chaudhary, Indra; Manandhar, Rija (Frontiers in Sociology, 2019)
The direct and indirect impacts of global climate change entail serious consequences for global biophysical and social systems, including the health, wellbeing and sustainability of communities. These impacts are especially serious for vulnerable groups in economically developing societies. While climate change is a global phenomenon, it is at the local level that impacts are most felt, and from where responses to climate change are enacted. It is increasingly urgent that communities possess the capacity to respond to climate change, now and in the future. Community representations of climate-relevant issues are critical to underpinning responses. Environmental representations do not directly reflect actual physical conditions but are interpreted through social and cultural layers of understanding that shape environmental issues. This paper investigates environmental and climate-relevant perceptions within two communities in the Terai region of Nepal; the city of Bharatpur and the village of Kumroj in Chitwan Province. Following mixed findings on levels of climate change awareness in Nepal, we set out to explore perspectives on the environment and climate change awareness by conducting 30 qualitative interviews with local people. They study found that issues linked to sanitation and cleanliness were most important in both communities, while reports of temperature and weather changes were less common and typically linked to local causes rather than climate change. Imagined futures were also closely related to current environmental issues affecting communities and did not discuss climate change, though temperature and weather changes were anticipated. However, when talk of climate change was deliberately elicited, participants displayed their awareness, though this was rarely linked to local conditions. We conclude that, in light of other pressing local issues, climate change is yet to penetrate the environmental representations of some communities and there is a need to address the disconnect between local issues and global climate change. Making climate change relevant at the local level by connecting to salient local issues and co-benefits comprises an important step in bridging the gap between more global awareness and its relevance more locally, particularly for communities at risk.